Study on Related Courses to Help Undergraduate Students Write Research Reports: A Curriculum Evaluation - Eny Winarti (Intelektual Pustaka Media Utama, 2014)
From the experience of joining the boards in the students’ research report defence, teaching education research methodology, and classroom action research, the researcher indicated that students had challenges related with the logic of research methods and academic research writing. These findings encouraged the researcher to study the courses that have potential in helping students writing their research reports. To study the courses, the researcher analysed related documents, such as syllabi and lesson plans. The researcher also interviewed teachers and students to clarify the relevance of the syllabi and the classroom learning. The results of the study indicated that logic, academic writing, statistics, research methodology, and classroom action research had the potential of helping the students write their research report. The researcher also indicated that the content of the courses should have been more helpful. The fact, however, was that the students still had challenges understanding the materials after taking the courses. Further study about this fact is then recommended.